2013
DOI: 10.1371/journal.pone.0082432
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Metabolite Profiling Reveal Specific Alterations in Bacterial Community Structure and Environment in the Cystic Fibrosis Airway during Exacerbation

Abstract: Chronic polymicrobial infections of the lung are the foremost cause of morbidity and mortality in cystic fibrosis (CF) patients. The composition of the microbial flora of the airway alters considerably during infection, particularly during patient exacerbation. An understanding of which organisms are growing, their environment and their behaviour in the airway is of importance for designing antibiotic treatment regimes and for patient prognosis. To this end, we have analysed sputum samples taken from separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 39 publications
(57 reference statements)
6
84
0
1
Order By: Relevance
“…Antibiotic treatment quickly eliminated these bacteria, indicating that the CF microbial community was dynamic through exacerbation events in this patient. Similar signatures of microbial fermentation have been described in other studies , including in exacerbation samples (Twomey et al, 2013), and the anaerobe Gamella was the most discriminate genus between exacerbation and stable samples in a previous microbiome study (Carmody et al, 2013). In light of these results, we propose that the CAM, originally described by Conrad et al (2012), should be focused on microbial physiology.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Antibiotic treatment quickly eliminated these bacteria, indicating that the CF microbial community was dynamic through exacerbation events in this patient. Similar signatures of microbial fermentation have been described in other studies , including in exacerbation samples (Twomey et al, 2013), and the anaerobe Gamella was the most discriminate genus between exacerbation and stable samples in a previous microbiome study (Carmody et al, 2013). In light of these results, we propose that the CAM, originally described by Conrad et al (2012), should be focused on microbial physiology.…”
Section: Resultssupporting
confidence: 85%
“…Some studies find little change (Fodor et al, 2012;Deschaght et al, 2013;Price et al, 2013), while others are finding fluctuations in anaerobic microbial abundance (Carmody et al, 2013;Deschaght et al, 2013;Twomey et al, 2013;Zemanick et al, 2013). The WinCF system demonstrated that obligate anaerobes are abundant prior to exacerbation and actively fermenting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the putrescine concentration was reported to be 3 mM in urine (11), whereas it was shown to be up to 0.2 mM in sputum samples from CF patients (39,40). However, it is difficult to predict the local concentration of putrescine and other polyamines in the lung of CF patients, as infection alters the rheology of the mucus and the lung environment (41).…”
Section: Figmentioning
confidence: 99%
“…However, it is difficult to predict the local concentration of putrescine and other polyamines in the lung of CF patients, as infection alters the rheology of the mucus and the lung environment (41). Moreover, putrescine levels increase dramatically (by 10-fold or more) during exacerbations of bacterial infections in CF patients (39,40). Hence, the concentrations used in this study could potentially resemble the physiological situation in certain body compartments.…”
Section: Figmentioning
confidence: 99%